Effect of nitrogen nutrition on nitrate dynamics of green pea - Nádasy, Erzsébet (Acta Biologica Szegediensis, 2002)
We studied the accumulation and dynamics of nitrate in green pea using rising rates of N-fertilisers and different nitrogen forms: nitrate, ammonium and together ammonium plus nitrate. The pot experiments were set up in greenhouse three planting dates with "Rajnai törpe" green pea variety. Samples were collected from the leafy stemat the growth stages of 4-6 leaves, in blossoming, and at maturity. Seed and pod samples were also analysed. We established that nitrate content of young pea plants was higher than that of the older ones at the optimal nitrogen nutrition levels. Nitrate-N stored increased throughout the growing season when N-supply was more than the optimum. The rising N-rates increased the nitrate content of leafy stems. Nitrate concentration of seed was little, but in pod was high over optimal N-supply. Nitrogen forms influenced the nitrate accumulation of leafy stem, seed and pod in different ways.